Adoption of musharakah financing model for the long term development of Small and Medium Sized Enterprises (SMES) - Abd Rahman, Nur Hasnida; Mohammed, Mustafa Omar (Ministry of Higher Education, Sultanate of Oman, 2017)
One of the important issues that have been discussed in the study of Small and Medium Enterprise ("SMEs") is their difficulty in getting access to external financing, particularly from the banking institutions. This problem occurs because the banking institutions are predominantly debt based financing system which requires SMEs to fulfill banking requirements of providing adequate collateral and payment of high interest rates. SMEs inability to fulfill these requirements obliges them to rely heavily on internal financing and this limits their long-term growth and development. As financing is crucial to ensure SMEs' long-term growth and development, this study has been conducted to examine the potential of Musharakah as a viable alternative financing for SMEs. Accordingly, the Musharakah financing model was developed and a survey among SMEs firms in Malaysia was conducted to validate the potential of Musharakah financing model for SMEs. The results show that Musharakah financing has potential in providing SMEs' with a greater access to financing. Therefore, the model needs to be given a premier attention so that SMEs will have greater access to financing for their long-term growth and expansion.